Neurotherapy : Progress in Restorative Neuroscience and Neurology : proceedings of the 25th international summer school of brain research, held at the Royal Netherlands Academy of Arts and Sciences, Amsterdam, the Netherlands, August 25-28, 2008 - Verhaagen, Joost (Progress in brain research, 2009)
This book focuses on the exciting recent progress in restorative neurology and neuroscience. The book includes chapters on major neurodegenerative disorders of the brain and the visual system, including Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis, Huntington's disease, macula degeneration, retinitis pigmentosa, glaucoma, spinal cord trauma, and multiple sclerosis. The primary goal of the book is to give an overview of new developments in translational research and in potential therapeutic strategies including stem cell therapy, immunotherapy, gene therapy, pharmacotherapy, neuroprotheses and deep brain stimulation. * Provides the reader with a unique overview over all aspects of new advances in the therapy of neurological and psychiatric disorders * Covers all levels of biological organization including novel molecular and cellular targets, electrophysiological, anatomical and behavioural substrates of neurodegeneration and the application of whole brain in vivo imaging * Broad focus with contributions by the top scientists worldwide in the respective disciplines.